PERFORMANCE REPORT ANALYSIS (LAKIN) AT THE CENTER FOR THE IMPLEMENTATION OF AGRICULTURAL INSTRUMENT STANDARDS (BPSIP) SOUTHEAST SULAWESI - Waode Alnur Mulia; Muntu Abdullah; Nur Asni (RADJA PUBLIKA, 2026)
This study aims to analyze the 2023 and 2024 Performance Reports (LAKIN) of the Southeast Sulawesi Agricultural Research and Development Agency (BPSIP) using an agency theory approach. The method used is descriptive qualitative, with data collection techniques through official document studies and interviews with employees involved in the LAKIN preparation. The results show that the 2023 achievement was very high, at 161.53%, with all indicators exceeding the target. Conversely, in 2024, there was a decline in achievement to 88.51%, influenced by low agricultural instrument production, extreme weather, and budget revisions. In the context of agency theory, LAKIN serves as a medium for agent accountability to the principal, as well as a control tool for task implementation. Despite the decline in achievement, the reporting process still reflects the accountability and transparency of the agency's performance.